ANALISIS KOMODITAS UNGGULAN PERIKANAN TANGKAP DI KABUPATEN REMBANG - Kohar, Abdul; Paramartha, Danta (Jurnal Harpodon Borneo, 2012)
The determination of superior commodities is needed for figuring out which ones are superior commodities and which ones are not. The superior commodities are expected to give greater profit than the other commodities. This study therefore aims to figure out the superior fisheries commodities which give contributions to the economy of Rembang regency. The method used in this study is descriptive. The sampling technique used in this study is purposive sampling. The data analysis instruments which were used are Location Quotient (LQ), Analysis of Shift Share (ASS), Specialization Analysis (SI), and Analitical Hierarchy Process (AHP). From the result of study it can be concluded that the superior fisheries commodities of Rembang regency which become the best products are scad (Decapterus russeli), yellowstripe scad (Selaroides leptolepis), and mackerel (Rastrellinger sp). The main factor which determines how those fish belong to superior commodities or not are the AHP analysis, that is, the adequacy of supply. The sub-sector of catch fisheries in Rembang regency has the LQ score of 5,05 in 2009. It shows that the sub-sector of catch fisheries is the basic sector which is very influencing the contribution of the economy in Rembang regency.  Key words: Superior Commodities, Fisheries, Analitical Hierarchy Process, Rembang Regency.